Academic dishonesty in online classes: Investigating self-reports using McCabe’s Academic Integrity Survey - Theresa Anne Nadine Lichauco; Ashley Molina; Dennis Tengco; Micah Francine Vidallo (Journal of Social, Humanity, and Education, 2023)
Purpose: To investigate the cause of academic dishonesty in online higher education in the Philippines during the COVID-19 pandemic. Research methodology: A descriptive-analytical study was conducted in a Manila-based higher education institution using McCabe's Academic Integrity Survey Report (2010) to collect data from 360 first- and second-year students. Results: While institutional policies were perceived as high, a low positive correlation was found between policy awareness and the tendency to engage in academic dishonesty in one category. Plagiarism-detecting software may deter some forms of cheating; however, opportunities for other forms of academic misconduct still exist. The prevalence of academic misconduct was higher among second-year students, indicating the normalization of such behavior among peers. Limitations: The study was conducted at one institution and may not be generalizable to other settings. Contribution: This study provides insights into the prevalence of academic misconduct and its contributing factors, highlighting the need for continued efforts to prevent and address academic dishonesty in online learning environments. Novelty: This study sheds light on the challenges in maintaining academic integrity during the COVID-19 pandemic and the importance of addressing academic misconduct in online higher education.